Composite wire and preparation method thereof

By adopting a multi-layer casing structure with copper core, stainless steel layer and silver layer in the wire, combined with surface treatment and vacuum annealing technology, the problems of poor oxidation resistance and insufficient strength at high temperatures are solved, and efficient conductivity is achieved and low-cost composite wire preparation.

CN116052921BActive Publication Date: 2025-01-14INST OF ELECTRICAL ENG CHINESE ACAD OF SCI
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211230622.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-30
Publication Date
2025-01-14
Estimated Expiration
2042-09-30

AI Technical Summary

Technical Problem

The existing conductors have poor oxidation resistance and insufficient strength at high temperatures, resulting in high manufacturing costs and reduced conductivity, making it difficult to meet the needs of industrial applications such as aviation and aerospace.

Method used

Using a multi-layer casing structure composite wire composed of copper core, stainless steel layer and silver layer, it is prepared through surface treatment and vacuum annealing to ensure the close bond between the stainless steel layer and Cu and Ag, forming a dense oxide film to improve resistance. Oxidation performance and improve conductivity and strength through drawing and recombination technology.

Benefits of technology

It realizes the stability of maintaining conductive properties at high temperatures, reduces the cost of conductor manufacturing, improves high-temperature oxidation resistance and strength, and meets the needs of industrial applications such as aviation and aerospace.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116052921B_ABST
    Figure CN116052921B_ABST
Patent Text Reader

Abstract

The present invention discloses a composite wire, which comprises a copper core, a stainless steel layer and a silver layer from the inside to the outside. The present invention also discloses a method for preparing the composite wire. In the composite wire of the present invention, part of Ag is replaced by Cu, which reduces the volume fraction of Ag and the preparation cost; stainless steel (SS) is selected as the intermediate material, which is not miscible with Cu and Ag, and is cheaper than Ag and Cu, and has higher strength; at the same time, stainless steel has good high-temperature oxidation resistance, and can also avoid the reaction of Cu and Ag at high temperature, preventing the reduction of electrical conductivity. When preparing the composite wire of the present invention, the stainless steel and the Cu rod are first drawn tightly to obtain a good Cu / SS interface bonding, and then the wire is inserted into an Ag tube for a second drawing to obtain a good SS / Ag interface bonding; the operation is simple, the cost is low, and the volume fraction of the components can be changed to obtain composite wires with different conductivity and strength combinations.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of wire preparation, and in particular to a composite wire and a preparation method thereof. Background Art

[0002] The preparation of composite wires with high temperature oxidation resistance, high strength and high conductivity is of great significance for many industrial applications such as aviation, aerospace and national defense. For example, the Bi-2212 high temperature superconducting wire used in nuclear fusion devices needs to be heat treated under high temperature (890°C), high pressure and oxygen environment. After heat treatment, the wire becomes soft and needs to be reinforced to improve its mechanical strength. The reinforced core is required to have high temperature oxidation resistance, high conductivity and high strength.

[0003] Existing studies have shown that Ag has good electrical conductivity, is resistant to oxidation at high temperatures, and has good compatibility with Bi2212 high-temperature superconducting wires, making it a good reinforcing core material. However, since Ag is too expensive, the manufacturing cost of the wire is high, and the strength of Ag is not high enough; Cu has good electrical conductivity and mechanical strength, and is relatively cheap. Cu can be used to partially replace Ag to perform the conductive function and prepare Ag / Cu composite wires. Since copper and silver react and dissolve in each other at high temperatures, in order to prevent the reaction between the two from reducing the conductivity of the composite wire, a third component (X) needs to be placed between Cu and Ag as a barrier material to prepare a multi-layer sheath structure Ag / X / Cu composite wire. The selection of the third component is very important, and the selection requirements include no reaction and dissolution with Cu and Ag, resistance to high-temperature oxidation, low cost and high strength.

[0004] Therefore, how to obtain a composite wire that has the advantages of high temperature oxidation resistance, high conductivity and high strength, and low manufacturing cost, is still a technical problem that needs to be solved urgently in this field. Summary of the invention

[0005] Therefore, the technical problem to be solved by the present invention is to overcome the defects of the existing wires, such as poor high temperature oxidation resistance and insufficient strength, thereby providing a composite wire and a preparation method thereof.

[0006] To this end, the present invention adopts the following technical solutions:

[0007] The invention provides a composite wire material, which comprises a copper core, a stainless steel layer and a silver layer from the inside to the outside.

[0008] Further,

[0009] The copper core has a diameter of 0.1-10 mm;

[0010] The thickness of the stainless steel layer is 0.02-2 mm;

[0011] The thickness of the silver layer is 0.05-10 mm.

[0012] Preferably

[0013] The copper core has a diameter of 0.3-6 mm;

[0014] The thickness of the stainless steel layer is 0.04-0.5 mm;

[0015] The thickness of the silver layer is 0.08-5 mm.

[0016] Further, the stainless steel includes one of 201, 202, 302, 303, 304, 304L, 316, 316LN, 321, 409, 410, 420, 430 or 436 grades of stainless steel;

[0017] The copper includes one of T1, T2, T3, C11000, C11100, C11300, C11400, C11500, C1100, TU1, TU2, C10200, C1020, TP1, TP2, C12000, C12200, C14500, C14700, C15000, C1201 or C1220 grades of copper.

[0018] Preferably, the stainless steel comprises one of 304, 316 or 316LN grades of stainless steel;

[0019] The copper comprises one of TU1, TU2, T1 or T2 grades of copper.

[0020] The present invention also provides a method for preparing the composite wire, comprising the following steps:

[0021] S1: Select copper rods, stainless steel tubes and silver tubes for surface treatment;

[0022] S2: annealing the treated stainless steel tube under vacuum conditions;

[0023] S3: inserting the copper rod into the annealed stainless steel tube for the first drawing and compounding to obtain an intermediate wire with a stainless steel-coated copper core;

[0024] S4: After the intermediate wire is inserted into the silver tube, it is drawn and compounded for the second time to obtain a composite wire.

[0025] Furthermore, step S4 also includes the step of annealing when the deformation amount of the intermediate wire is 50%-60%, the annealing temperature is 750-850° C., and the annealing time is 120 min.

[0026] In step S2, the annealing temperature is 800-1300° C., and the annealing time is 30-240 min.

[0027] The inner diameter of the stainless steel tube is 0.2-0.4 mm larger than the outer diameter of the copper rod, and the inner diameter of the silver tube is 0.2-0.4 mm larger than the outer diameter of the intermediate wire.

[0028] The surface treatment in step S1 is to remove the oxide layer on the surface of the copper rod, the stainless steel tube and the silver tube.

[0029] The technical solution of the present invention has the following advantages:

[0030] (1) In the composite wire of the present invention, Cu is used to replace a portion of Ag, which reduces the volume fraction of Ag in the wire and the cost of wire preparation; stainless steel is selected as the intermediate material. The main elements in stainless steel are not miscible with Cu and Ag. Moreover, compared with Ag and Cu, stainless steel is a well-known cheap material and has high strength. More importantly, compared with other pure metals, stainless steel has good high-temperature oxidation resistance, thereby preventing the composite wire from oxidizing and failing at high temperatures; it can avoid the reaction of Cu and Ag at high temperatures, prevent the reduction of conductivity, and maintain the high conductivity of Cu and Ag.

[0031] (2) The electrical conductivity of the composite wire of the present invention mainly comes from Cu and Ag. The electrical conductivity of stainless steel itself is relatively poor, and the processing deformation ability of stainless steel is worse than that of Cu and Ag. Therefore, the thickness of stainless steel in the composite wire needs to be limited. Too thick will affect the electrical conductivity and processing performance. Too thin will cause cracks and gaps in the stainless steel layer after drawing and deformation, and it will be unable to separate Cu and Ag, thereby limiting the reaction of Cu and Ag at high temperature.

[0032] (3) The reason why stainless steel has good high-temperature oxidation resistance is that a dense oxide film can be formed on its surface to passivate the surface. However, if it is exposed to oxygen for a long time at high temperature, it will often cause severe corrosion. With the stratification and shedding of the oxide, the dense oxide layer on the surface cannot be completely covered, resulting in serious corrosion failure. In the present invention, the composite wire is a multi-layer sleeve structure. After drawing, the stainless steel and the outer Ag layer have a good interface bonding. On the one hand, the Ag in the outer layer reduces the corrosion of the stainless steel by oxygen. On the other hand, the compressive stress of the Ag layer on the oxide on the surface of the stainless steel inhibits the stratification and shedding of the oxide, greatly improving the oxidation resistance at high temperature, so that the composite wire has excellent high-temperature oxidation resistance.

[0033] (4) In the preparation of the composite wire of the present invention, since stainless steel has higher strength than Cu and Ag and is difficult to deform, it is necessary to first draw the stainless steel and Cu rods to make them tightly bonded and obtain a good Cu / SS interface bond. Then, it is inserted into the Ag tube for a second drawing to make the Ag tube and the stainless steel tube tightly bonded and obtain a good SS / Ag interface bond.

[0034] (5) The present invention performs vacuum annealing on the stainless steel before drawing, the purpose of which is to soften the stainless steel, improve its plastic deformation ability, and prevent cracks from forming during the drawing process.

[0035] (6) In the present invention, when the deformation of the sample reaches 50%-60% during the second drawing and compounding, it is annealed to prevent the formation of cracks; the annealing temperature should be higher than the recrystallization temperature that occurs during the annealing process. If the holding time is too long, it will cause grain growth and strength reduction, and if the time is too short, the purpose of recrystallization softening cannot be achieved.

[0036] (7) The preparation method provided by the present invention is simple to operate and has low cost. In addition, the volume fractions of Cu, stainless steel and Ag can be matched by the preparation method, so that composite wires with different conductivity and strength combinations can be obtained during the production process. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0038] Figure 1 is a metallographic photograph of the composite wire obtained in Example 1 of the present invention, wherein (A) is a straight section and (B) is a cross section;

[0039] Figure 2 This is a scanning electron microscope photograph of the composite wire obtained in Example 1 of the present invention after annealing;

[0040] Figure 3 This is a photo of the composite wire obtained in Comparative Example 1 of the present invention;

[0041] Figure 4 The composite wire obtained in Comparative Example 4 of the present invention, wherein (A) is a photo of the appearance of the composite wire, and (B) is a metallographic photo of the straight section;

[0042] Figure 5 The composite wire obtained in Comparative Example 5 of the present invention, wherein (A) is an appearance photo of the composite wire, and (B) is a metallographic photo of a straight section.

[0043] Reference numerals:

[0044] 1-Copper core; 2-Stainless steel layer; 3-Silver layer. DETAILED DESCRIPTION

[0045] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0046] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0047] Example 1

[0048] This embodiment provides a composite wire, and its preparation method comprises the following steps:

[0049] (1) Take a T1 brand Cu rod with a diameter of 3.8 mm, a 304 stainless steel tube with an outer diameter of 4.5 mm and a thickness of 0.2 mm, and an Ag tube with an outer diameter of 5.0 mm and a thickness of 0.5 mm.

[0050] The oxide scales on the surface of the Cu rod and the stainless steel tube were cleaned respectively with 5% dilute hydrochloric acid, and then ultrasonically cleaned in alcohol and acetone.

[0051] (2) The surface treated stainless steel tube was annealed under vacuum at a temperature of 1000°C, a holding time of 120 min, and a pressure of 5×10 -3 Below Pa.

[0052] (3) The Cu rod is inserted into the annealed stainless steel tube for the first drawing and compounding to obtain an intermediate wire with a stainless steel-coated copper core.

[0053] In the intermediate wire after the first drawing and compounding, the diameter of the Cu rod is 3.4 mm, the outer diameter of the stainless steel tube is 4.2 mm, and the thickness is 0.2 mm.

[0054] (4) The intermediate wire is inserted into the Ag tube, and then a second drawing and compounding is performed to obtain a composite wire. When the deformation of the sample reaches 50%-60%, it is annealed at a temperature of 800°C and a holding time of 120 minutes.

[0055] In the composite wire after the second drawing and compounding, the diameter of the Cu core is 1.04 mm, the outer diameter of the stainless steel layer is 1.136 mm, the thickness is 0.048 mm, and the outer diameter of the Ag layer is 1.3 mm, and the thickness is 0.087 mm.

[0056] Based on the total volume of the composite wire, the volume fraction of Cu is 64%, the volume fraction of stainless steel is 11%, and the volume fraction of Ag is 25%. Figure 1 The metallographic photograph of the composite wire is shown. Figure 1 (A) is a straight section. Figure 1 (B) is a cross section, and the composite wire comprises a copper core 1, a stainless steel layer 2 and a silver layer 3 from the inside to the outside.

[0057] The composite wire was annealed at 893°C for 120 min in air to obtain a composite wire with unchanged appearance and microstructure. The scanning electron microscope photo is shown in FIG. Figure 2 As shown, the interfaces of Cu, SS, and Ag are clear and complete, without obvious reaction and diffusion.

[0058] Example 2

[0059] This embodiment provides a composite wire, and its preparation method comprises the following steps:

[0060] (1) Take a T2 grade Cu rod with a diameter of 1.2 mm, a 304 stainless steel tube with an outer diameter of 1.5 mm and a thickness of 0.1 mm, and an Ag tube with an outer diameter of 2.5 mm and a thickness of 0.5 mm.

[0061] The oxide scales on the surface of the Cu rod and the stainless steel tube were cleaned respectively with 5% dilute hydrochloric acid, and then ultrasonically cleaned in alcohol and acetone.

[0062] (2) The surface treated stainless steel tube was annealed under vacuum at a temperature of 1000°C, a holding time of 120 min, and a pressure of 5×10 -3 Below Pa.

[0063] (3) The Cu rod is inserted into the annealed stainless steel tube for the first drawing and compounding to obtain an intermediate wire with a stainless steel-coated copper core.

[0064] In the intermediate wire after the first drawing and compounding, the diameter of the Cu rod is 1.1 mm, the outer diameter of the stainless steel tube is 1.3 mm, and the thickness is 0.1 mm.

[0065] (4) Insert the intermediate wire into the Ag tube, and then draw and composite for the second time to obtain the composite wire. When the deformation of the sample reaches 50%-60%, it is annealed at a temperature of 800°C and a holding time of 120 minutes.

[0066] In the composite wire after the second drawing and compounding, the diameter of the Cu core is 0.6 mm, the outer diameter of the stainless steel layer is 0.715 mm, the thickness is 0.057 mm, and the outer diameter of the Ag layer is 1.06 mm, and the thickness is 0.17 mm.

[0067] Based on the total volume of the composite wire, the volume fraction of Cu is 32%, the volume fraction of stainless steel is 14%, and the volume fraction of Ag is 54%.

[0068] Example 3

[0069] This embodiment provides a composite wire, and its preparation method comprises the following steps:

[0070] (1) Take a Cu rod with a diameter of 6 mm, a 304 stainless steel tube with an outer diameter of 6.5 mm and a thickness of 0.2 mm, and an Ag tube with an outer diameter of 9 mm and a thickness of 1.5 mm.

[0071] The oxide scales on the surface of the Cu rod and the stainless steel tube were cleaned respectively with 5% dilute hydrochloric acid, and then ultrasonically cleaned in alcohol and acetone.

[0072] (2) The surface treated stainless steel tube was annealed under vacuum at a temperature of 1000°C, a holding time of 120 min, and a pressure of 5×10 -3 Below Pa.

[0073] (3) The Cu rod is inserted into the annealed stainless steel tube for the first drawing and compounding to obtain an intermediate wire with a stainless steel-coated copper core.

[0074] In the intermediate wire after the first drawing and compounding, the diameter of the Cu rod is 5.5 mm, the outer diameter of the stainless steel tube is 5.9 mm, and the thickness is 0.2 mm.

[0075] (4) Insert the intermediate wire into the Ag tube, and then draw and composite for the second time to obtain the composite wire. When the deformation of the sample reaches 50%-60%, it is annealed at a temperature of 800°C and a holding time of 120 minutes.

[0076] In the composite wire after the second drawing and compounding, the diameter of the Cu rod is 5.1 mm, the outer diameter of the stainless steel tube is 5.35 mm, the thickness is 0.125 mm, and the outer diameter of the Ag tube is 7.65 mm, and the thickness is 1.15 mm.

[0077] Based on the total volume of the composite wire, the volume fraction of Cu is 44.5%, the volume fraction of stainless steel is 4.5%, and the volume fraction of Ag is 51%.

[0078] Comparative Example 1

[0079] This comparative example provides a composite wire. The difference between this comparative example and Example 3 is that Nb is used instead of stainless steel as the intermediate barrier layer. The preparation method thereof includes the following steps:

[0080] (1) Take a Cu rod with a diameter of 6 mm, a Nb tube with an outer diameter of 6.5 mm and a thickness of 0.2 mm, and an Ag tube with an outer diameter of 9 mm and a thickness of 1.5 mm.

[0081] The oxide scales on the surfaces of the Cu rod and the Nb tube were cleaned respectively with 5% dilute hydrochloric acid, and then ultrasonically cleaned in alcohol and acetone.

[0082] (2) The surface treated Nb tube was annealed under vacuum at a temperature of 1000°C, a holding time of 120 min, and a pressure of 5×10 -3 Below Pa.

[0083] (3) The Cu rod is inserted into the annealed Nb tube for the first drawing and compounding to obtain the intermediate wire with Nb-coated copper core.

[0084] In the intermediate wire after the first drawing and compounding, the diameter of the Cu rod is 5.5 mm, the outer diameter of the Nb tube is 5.9 mm, and the thickness is about 0.2 mm.

[0085] (4) Insert the intermediate wire into the Ag tube, and then draw and composite for the second time to obtain the composite wire. When the deformation of the sample reaches 50%-60%, it is annealed at a temperature of 800°C and a holding time of 120 minutes.

[0086] In the composite wire after the second drawing, the diameter of the Cu rod is 5.1 mm, the outer diameter of the Nb tube is 5.35 mm, and the thickness is 0.125 mm. The outer diameter of the Ag tube is 7.65 mm, and the thickness is 1.15 mm. Figure 3 As shown, due to the obvious oxidation of Nb, the produced oxide expands and causes the outer layer Ag to crack, resulting in the failure of the composite wire.

[0087] Based on the total volume of the composite wire, the volume fraction of Cu is 44.5%, the volume fraction of the Nb tube is 4.5%, and the volume fraction of Ag is 51%.

[0088] Comparative Example 2

[0089] This comparative example provides a composite wire, which differs from Example 2 in that the content of stainless steel is increased.

[0090] The preparation method thereof is as follows: a Cu rod with a diameter of 1.2 mm, a 304 stainless steel tube with an outer diameter of 1.9 mm and a thickness of 0.3 mm, and an Ag tube with an outer diameter of 3.2 mm and a thickness of 0.6 mm are taken. The intermediate preparation process is the same as that in Example 2. Finally, in the composite wire after the second drawing and compounding, the diameter of the Cu rod is 0.6 mm, the outer diameter of the 304 stainless steel tube is 0.9 mm, and the thickness is 0.15 mm. The outer diameter of the Ag tube is 1.24 mm and the thickness is 0.17 mm.

[0091] Based on the total volume of the composite wire, the volume fraction of Cu is 23%, the volume fraction of 304 stainless steel is 29.2%, and the volume fraction of Ag is 47%.

[0092] Comparative Example 3

[0093] This comparative example provides a composite wire, which differs from Example 2 in that the content of stainless steel is reduced.

[0094] The preparation method thereof is as follows: a Cu rod with a diameter of 1.2 mm, a 304 stainless steel tube with an outer diameter of 1.4 mm and a thickness of 0.015 mm, and an Ag tube with an outer diameter of 2.5 mm and a thickness of 0.5 mm are taken. The intermediate preparation process is the same as that in Example 2. Finally, in the composite wire after the second drawing and compounding, the diameter of the Cu rod is 0.6 mm, the outer diameter of the 304 stainless steel tube is 0.66 mm, and the thickness is 0.008 mm. The outer diameter of the Ag tube is 1.016 mm and the thickness is 0.2 mm.

[0095] Based on the total volume of the composite wire, the volume fraction of Cu is 35%, the volume fraction of 304 stainless steel is 1.88%, and the volume fraction of Ag is 63%.

[0096] Comparative Example 4

[0097] This comparative example provides a composite wire, which is different from Example 1 in that the stainless steel is not vacuum annealed before the first drawing and bonding.

[0098] Its preparation method comprises the following steps:

[0099] (1) Take a T1 brand Cu rod with a diameter of 3.8 mm, a 304 stainless steel tube with an outer diameter of 4.5 mm and a thickness of 0.2 mm, and an Ag tube with an outer diameter of 5.0 mm and a thickness of 0.5 mm.

[0100] The oxide scales on the surface of the Cu rod and the stainless steel tube were cleaned respectively with 5% dilute hydrochloric acid, and then ultrasonically cleaned in alcohol and acetone.

[0101] (2) The Cu rod is inserted into the annealed stainless steel tube for the first drawing and compounding to obtain the intermediate wire with stainless steel coated copper core.

[0102] In the intermediate wire after the first drawing and compounding, the diameter of the Cu rod is 3.4 mm, the outer diameter of the stainless steel tube is 4.2 mm, and the thickness is 0.2 mm.

[0103] (3) Insert the intermediate wire into the Ag tube, and then perform a second drawing and compounding.

[0104] Since the stainless steel was not vacuum annealed before the first drawing and bonding, the plasticity of the stainless steel was poor. When the deformation of the sample reached 38%, Figure 4 As shown, Figure 4 As can be seen from (A), there are obvious micro cracks on the surface of the composite wire. Figure 4 From the metallographic photograph of the longitudinal section of the composite wire (B), it can be seen that the middle stainless steel layer has been broken and cannot play an effective barrier role.

[0105] Comparative Example 5

[0106] This comparative example provides a composite wire, which is different from Example 1 in that, during the second drawing and compounding, the sample is annealed when the deformation reaches 70%.

[0107] Its preparation method comprises the following steps:

[0108] (1) Take a T1 brand Cu rod with a diameter of 3.8 mm, a 304 stainless steel tube with an outer diameter of 4.5 mm and a thickness of 0.2 mm, and an Ag tube with an outer diameter of 5.0 mm and a thickness of 0.5 mm.

[0109] The oxide scales on the surface of the Cu rod and the stainless steel tube were cleaned respectively with 5% dilute hydrochloric acid, and then ultrasonically cleaned in alcohol and acetone.

[0110] (2) The Cu rod is inserted into the annealed stainless steel tube for the first drawing and compounding to obtain the intermediate wire with stainless steel coated copper core.

[0111] In the intermediate wire after the first drawing and compounding, the diameter of the Cu rod is 3.4 mm, the outer diameter of the stainless steel tube is 4.2 mm, and the thickness is 0.2 mm.

[0112] (3) Insert the intermediate wire into the Ag tube, and then draw and composite for the second time. When the sample deformation reaches 70%, it is annealed at 800°C for 120 minutes. Figure 5 As shown, Figure 5 As can be seen from (A), there are obvious micro cracks on the surface of the composite wire. Figure 5 From the metallographic photograph of the longitudinal section of the composite wire (B), it can be seen that the middle stainless steel layer has been broken and cannot play an effective barrier role.

[0113] Test example

[0114] The composite wires obtained in Examples 1-3 and Comparative Examples 2 and 3 were annealed in air at 893°C for 120 min to obtain wires with unchanged appearance and microstructure. The annealed composite wires were then subjected to performance tests, and the strength of the composite wires was tested in accordance with GBT228.1-2010 "Method for tensile test of metal materials at room temperature", and the conductivity was tested in accordance with GB / T 351-2019 "Method for measuring resistivity of metal materials". The results are shown in Table 1:

[0115] Table 1 Composite wire performance test

[0116]

[0117]

[0118] It can be seen that each embodiment of the present invention has excellent strength and conductivity. Compared with Example 2, although the strength of Comparative Example 2 is improved, its conductivity is greatly reduced. This is because the stainless steel content is too high, which affects the conductivity. Compared with Example 2, Comparative Example 3 is not only much weaker than Example 2 in strength, but also has a significantly reduced conductivity. This is because the stainless steel content is too low. After the stainless steel layer is too thin and drawn, cracks and gaps will appear, which cannot separate Cu and Ag, causing Cu and Ag to react at high temperature, affecting the strength and reducing the overall conductivity.

[0119] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A composite wire, characterized in that: From inside to outside, it is copper core, stainless steel layer and silver layer; The method for preparing the composite wire comprises the following steps: S1: Select copper rods, stainless steel tubes and silver tubes for surface treatment; S2: annealing the treated stainless steel tube under vacuum conditions; S3: inserting the copper rod into the annealed stainless steel tube for the first drawing and compounding to obtain an intermediate wire with a stainless steel-coated copper core; S4: inserting the intermediate wire into the silver tube and then drawing and compounding for the second time to obtain a composite wire; Wherein, in step S2, the annealing temperature is 800-1300°C, and the annealing time is 30-240min; The copper core has a diameter of 0.1-10 mm; The thickness of the stainless steel layer is 0.02-2 mm; The thickness of the silver layer is 0.05-10 mm; Step S4 also includes, during the second drawing and compounding, when the wire deformation is 50%-60%, an annealing step is performed, the annealing temperature is 750-850° C., and the annealing time is 30 to 240 minutes.

2. The composite wire according to claim 1, characterized in that The copper core has a diameter of 0.3-6 mm; The thickness of the stainless steel layer is 0.04-0.5 mm; The thickness of the silver layer is 0.08-5 mm.

3. The composite wire according to claim 1 or 2, characterized in that: The stainless steel comprises one of 201, 202, 302, 303, 304, 304L, 316, 316LN, 321, 409, 410, 420, 430 or 436 grades of stainless steel; The copper includes one of T1, T2, T3, C11000, C11100, C11300, C11400, C11500, C1100, TU1, TU2, C10200, C1020, TP1, TP2, C12000, C12200, C14500, C14700, C15000, C1201 or C1220 grades of copper.

4. The composite wire according to claim 3, characterized in that: The stainless steel comprises one of 304, 316 or 316LN grades of stainless steel; The copper comprises one of TU1, TU2, T1 or T2 grades of copper.

5. The method for preparing the composite wire according to any one of claims 1 to 4, characterized in that: The steps include: S1: Select copper rods, stainless steel tubes and silver tubes for surface treatment; S2: annealing the treated stainless steel tube under vacuum conditions; S3: inserting the copper rod into the annealed stainless steel tube for the first drawing and compounding to obtain an intermediate wire with a stainless steel-coated copper core; S4: After the intermediate wire is inserted into the silver tube, it is drawn and compounded for the second time to obtain a composite wire.

6. The method for preparing the composite wire according to claim 5, characterized in that: Step S4 also includes, during the second drawing and compounding, when the wire deformation is 50%-60%, an annealing step is performed, the annealing temperature is 750-850° C., and the annealing time is 30 to 240 minutes.

7. The preparation method according to claim 5, characterized in that: The inner diameter of the stainless steel tube is 0.2-0.4 mm larger than the outer diameter of the copper rod, and the inner diameter of the silver tube is 0.2-0.4 mm larger than the outer diameter of the intermediate wire.

8. The preparation method according to claim 5, characterized in that: The surface treatment in step S1 is to remove the oxide layer on the surface of the copper rod, the stainless steel tube and the silver tube.

Citation Information

Patent Citations

  • Silver-copper-iron composite conductive wire and preparation method thereof

    CN110711792A